Representational structures and psychopathology : analysis of spontaneous descriptions of self and significant others in patients with different mental disorders - Benedik, Emil (Array, 2009)
The article was designed to contribute to the empirical clarification of representational structures among adult psychiatric patients. According to psychoanalytic concepts, cognitive developmental psychology and attachment theory, various forms of adult psychopathology involve fundamental impairments in representational structures or cognitive-affective schemas. We conducted a study to research the structural characteristics of representations of self and significant others in patients with different, mostly severe mental disorders according to DSM-IV and Kernberg’s structural criteria for personality organizations